Analisis Faktor-Faktor yang Mempengaruhi Produksi Usahatani Nanas Pada Lahan Gambut di Kecamatan Panai Tengah Kabupaten Labuhanbatu - Setiawan, Budi Rezky; Sibuea, Muhammad Buhari; Pane, Erwin (Universitas Medan Area, 2019)
This study aims to determine how the influence of land area, number of seedlings, the number of labor and fertilizer simultaneously and partially on pineapple production in Panai Tengah sub-district Labuhanbatu Regency. This research was conducted in the Central Panai District Labuhan Batu District in April to June 2017. Determination of the location was done intentionally (purposive) with the consideration that the pineapple farming in Central Panai District is a farm carried out on the condition of the land with peat soil types and the results of their production have been has a characteristic as panai pineapple. This research is a descriptive study with a quantitative approach. The number of samples was 86 samples. The data used are primary and secondary data. Primary data obtained by interview using a questionnaire. While secular data uses data obtained from the agency. In this research, the initial step taken is to form an equation with the Cobb Doughlas function, then the equation is transformed in the form of a natural logarithm to facilitate multiple regression analysis using the SPSS 19.0 program. The results showed that the factors affecting pineapple production were land area, number of seeds, and number of workers.